2011
DOI: 10.1002/cyto.a.21028
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle dependent TN‐C promoter activity determined by live cell imaging

Abstract: The extracellular matrix protein tenascin-C plays a critical role in development, wound healing, and cancer progression, but how it is controlled and how it exerts its physiological responses remain unclear. By quantifying the behavior of live cells with phase contrast and fluorescence microscopy, the dynamic regulation of TN-C promoter activity is examined. We employ an NIH 3T3 cell line stably transfected with the TN-C promoter ligated to the gene sequence for destabilized green fluorescent protein (GFP). Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 38 publications
(27 reference statements)
1
28
0
Order By: Relevance
“…Independent analysis of live-cell data in an unsorted dish confirmed that the dimmest cells (corresponding to the lower log normal in Fig. S2A) proliferated at a rate that was 10% slower than the other cells (31). This observation is consistent with previous observations that expression of TN-C is associated with proliferating cells (28).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Independent analysis of live-cell data in an unsorted dish confirmed that the dimmest cells (corresponding to the lower log normal in Fig. S2A) proliferated at a rate that was 10% slower than the other cells (31). This observation is consistent with previous observations that expression of TN-C is associated with proliferating cells (28).…”
Section: Resultssupporting
confidence: 90%
“…Time-lapse fluorescence microscopy of live cells, in which individual cells were segmented and tracked over long times (31), reveals that TN-C promoter activity exhibits random fluctuations as well as cell cycle-dependent trends. On average, cells approximately double their total fluorescence before dividing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first measured the overlap between test and control segmentations using area similarity (AS) (49)(50)(51)(52) …”
Section: Performance Assessmentmentioning
confidence: 99%
“…Live cell imaging allows examination of spatial and temporal information about gene expression in colonies and between colonies (Singer et al, 2014; Bajcsy et al, 2016; Halter et al, 2011; Barbaric et al, 2014; Chan et al, 2009). Meaningful quantification requires sampling a large population of cells and colonies, and because the area of individual colonies can be larger than the FOV with a 10× objective lens, tracking a colony over time as it grows and moves requires that many adjacent fields be examined and stitched together.…”
Section: Discussionmentioning
confidence: 99%